Ethics in research / Dr. Dang Merduwati Hashim - Hashim, Dang Merduwati (Faculty of Information Management, 2009)
All researchers are required to do their research ethically while ensuring the validity and reliability of their data. Based on the The Nuremberg Code (1947), The Helsinki Declaration (1964) and Belmont Report, the ethics in research is discussed briefly. Four (4) examples of research ethics for qualitative researchers are also discussed.